1980
DOI: 10.1111/j.1365-2621.1980.tb06503.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Selective Enrichment Media for the Isolation of Salmonella From Mechanically Deboned Poultry Meat

Abstract: Two selective enrichment media were developed for the isolation of salmonellae from foods. The first, experimental broth 1, contained magnesium chloride and sodium cholate as the selective ingredients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…During the ini-tial portion of this study, samples were enriched in tetrathionate with iodine a and 3MC broth, a laboratory-prepared medium that, when compared with tetrathionate and selenite broths, was superior for isolation of salmonellae from poultry meat and that allowed increased growth of S. choleraesuis. 2,4 After the beginning of the study, and in-house trial demonstrated that Rappaport-Vassiliadis broth was superior to 4 other enrichment media, including tetrathionate and 3MC broths, for recovery of S. choleraesuis from experimentally inoculated pig feces (data not shown). For that reason, Rappaport-Vassiliadis R10 broth a was used for enrichment of source 2 samples and approximately 1 third of the source 1 samples.…”
Section: Comparison Of Conventional and Delayed Secondary Enrichment mentioning
confidence: 99%
“…During the ini-tial portion of this study, samples were enriched in tetrathionate with iodine a and 3MC broth, a laboratory-prepared medium that, when compared with tetrathionate and selenite broths, was superior for isolation of salmonellae from poultry meat and that allowed increased growth of S. choleraesuis. 2,4 After the beginning of the study, and in-house trial demonstrated that Rappaport-Vassiliadis broth was superior to 4 other enrichment media, including tetrathionate and 3MC broths, for recovery of S. choleraesuis from experimentally inoculated pig feces (data not shown). For that reason, Rappaport-Vassiliadis R10 broth a was used for enrichment of source 2 samples and approximately 1 third of the source 1 samples.…”
Section: Comparison Of Conventional and Delayed Secondary Enrichment mentioning
confidence: 99%
“…Samples were enriched by one of three methods: (i) overnight preenrichment in tryptic soy broth (TSB; Difco Laboratories Inc., Detroit, Mich.) at 37°C and overnight enrichment in Rappaport-Vassiliadis 10 broth (RV10; Difco) at 42°C (TSB-RV10 enrichment method), (ii) overnight preenrichment in a laboratory-prepared medium previously designated 3MC broth (2,20) at 37°C and overnight enrichment in RV10 at 42°C (3MC-RV10 enrichment method), and (iii) direct overnight enrichment in RV10 at 42°C (with no secondary enrichment) (RV10 enrichment method). All samples were collected within 100 mi of the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Another factor, which may have contributed to the increased efficiency of the MFDI technique, was the use of the mannitol-magnesium Greenwood et al (1980) have demonstrated that MMS broth was significantly better than selenite and tetrathionate broths in the isolation of salmonellae from MDPM. Further, pseudomonads and coliforms, which caused a great deal of interference in the conventional cultural method, did not pose any problems in the MFDI method.…”
Section: Resultsmentioning
confidence: 98%
“…Unless otherwise stated, all bacteriological media and ingredients for media were obtained from Difco Laboratories, Detroit, MI. The mannitol-magnesium chloride-sodium cholate (MMS) medium was prepared according to the procedure described by Greenwood et al (1980). A modified formulation of dulcitol -brilliant green-novobiocin (DBN) semi-solid medium of Swaminathan et al (1978) was used in the MFDI procedure and was prepared as follows: dulcitol 4.0 g, proteose peptone 12.0 g, yeast extract 3.0 g, sodium chloride 5.0 g, sodium thiosulfate 5.0 g, bile salts 15.0 g, ferric ammonium citrate 1.5 g, sodium desoxycholate 2.0 g, and agar 4.0 g were weighed into a 1500 ml Erlenmeyer flask and 1000 ml of distilled water were added.…”
Section: Mechanicallymentioning
confidence: 99%